NYIT Energy Advisory Service implementation plan - Tenen, G. B. (New York Inst. of Tech., Old Westbury (USA). Center for Energy Policy and Research, 1976)
The philosophic basis and proposed implementation of an energy outreach program were set forth in a proposal of December 5, 1975 and in a revised proposal and budget of March 22, 1976, submitted after consultation with ERDA officials. The objectives and scope of work for the initial ten-month period presently contracted, and for the balance of the proposed two-year program, are summarized in the ERDA document ''Project: Outreach Program for Energy Information Dissemination in Adjacent Areas of New York, New Jersey, and Connecticut''. A copy is included at the end of this report. The implementation plan set forth here specifies the nature and the time schedule of the work to be accomplished throughout the tem-month and the two-year periods. In order to disseminate information to target audiences, the institute will utilize various energy technology channels of communications, including, the Energy Information Center; NYIT Energy Hot Line; Metropolitan Regional Council Television Seminars; Referral Services; press releases; technical assisance teams; newspaper question-and-answer columns; traveling displays; contests; conferences; radio spots; volunteers; and Center for Energy Policy and Research Periodical. All energy topics are included, but priority in the short term will be given to energy management programs for small commercial/industrial plants; residential building insulation and weatherization; solar hot water heating and solar space heating systems; and heat pumps. (MCW)